Effects of dimethylsulfoxide and pentoxifylline in the vitality of cutaneous flaps in rats - Pedretti,Stephanie Luzia da Costa (2017)
ABSTRACT Objectives: to verify the influence of dimethylsulfoxide and pentoxifylline on the vitality of cutaneous flaps in rats and the tissue repair process. Methods: were studied 30 Wistar rats, submitting them to a 2cm wide by 8cm long dorsal cutaneous flap, of caudal base. We distributed the animals in three groups: Control Group (n=10) with application gauze moistened with 0.9% Saline in the flap bed for 30 seconds; Dimethylsulfoxide group (n=10), with administration of 1ml of 5% dimethylsulfoxide divided into five injections of 0.2ml in the transition of the flap segments; Pentoxifylline group (n=10), with administration of pentoxifylline 20mg/kg, diluted to 1ml and divided into five injections of 0.2ml in the transition of the flap segments. Drugs were administered intraoperatively, in a single dose and subcutaneously. We observed the skin flaps for changes in color and texture. On the 10th postoperative day, we checked the dimensions of viable and necrotic tissues, followed by excision of the specimen for histological analysis. Results: the measurements of length of the viable and necrotic tissues between groups showed no differences. Histological analysis showed that the Dimethylsulfoxide group presented neovascularization, inflammatory infiltrate with leukocytes and more structured conjunctival stroma. The Pentoxifylline group showed neovascularization and inflammatory infiltrate, with moderate to intense granulation. The control group evolved with a higher rate of necrosis in the distal segment. Conclusion: dimethylsulfoxide and pentoxifylline influenced the vitality of the flap and the tissue repair process. However, they did not prevent necrosis macroscopically.